2016
DOI: 10.21577/0103-5053.20160279
|View full text |Cite
|
Sign up to set email alerts
|

Volatile Organic Compounds (VOCs) Emitted by Ilex paraguariensis Plants are Affected by the Herbivory of the Lepidopteran Thelosia camina and the Coleopteran Hedypathes betulinus

Abstract: The profile of volatiles emitted by Ilex paraguariensis, leaves of which are used to produce a popular South American tea, were identified and compared among treatments. Headspace collections were performed for 24-72 hours for control, mechanical damage (MD), herbivory by larvae of Thelosia camina (TC), and by adults of Hedypathes betulinus (HB). Based on gas chromatography-mass spectrometry (GC-MS) and gas chromatography-Fourier transform infrared (GC-FTIR) analyses, 20 compounds were identified, totaling abo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
5
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 23 publications
1
5
0
Order By: Relevance
“…Similarly, 1,2,3-trimethylbenzene was abundant in approximately 2-fold higher amounts in the soil of infested “BB1” compared to controls. This result is consistent with increased emission rates of this volatile from tropical plants infested by leaf herbivores (Martins et al, 2017). In good agreement with our results, these authors also observed higher release of the aldehydes nonanal and decanal, which therefore also seem to be involved in biotic stress defense.…”
Section: Discussionsupporting
confidence: 85%
See 2 more Smart Citations
“…Similarly, 1,2,3-trimethylbenzene was abundant in approximately 2-fold higher amounts in the soil of infested “BB1” compared to controls. This result is consistent with increased emission rates of this volatile from tropical plants infested by leaf herbivores (Martins et al, 2017). In good agreement with our results, these authors also observed higher release of the aldehydes nonanal and decanal, which therefore also seem to be involved in biotic stress defense.…”
Section: Discussionsupporting
confidence: 85%
“…There is not much information on these compounds in the literature, although emission of some of them has been reported for other plants. Isopropyl myristate, trimethylbenzene, and heptadecane, for example, are emitted by several plant species, but their functions are not known yet (Thompson and Gornall, 1995; Weissteiner, 2010; Yang et al, 2014; Martins et al, 2017). According to the electrophysiological studies of Eilers et al (2012), the common cockchafer is not able to perceive β-pinene so that lower emission of this compound cannot be related to the interaction with this herbivore, supposing that the forest cockchafer used in the present study has similar capabilities.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In a study by Marquez et al [ 11 ], they observed that geranyl acetate (9.38 µg g −1 ), linalool (4.78 µg g −1 ) and isomers ( E , E )- and ( E , Z )-2,4-heptadienal (3.60 and 1.21 µg g −1 ) were the most abundant in Yerba mate leaves. Conversely, Martins et al [ 12 ] conducted a study on the volatile compounds released in relation to mechanical damage and herbivore exposure. In the control group, which was I. paraguariensis , the main volatile compounds reported were decanal, nonanal, and limonene.…”
Section: Resultsmentioning
confidence: 99%
“…From the 2000s onwards, more and more DIVs comprising methyl jasmonate (MeJA) in sagebrush (Preston et al, 2001), linalool and linalool oxide in damaged wheat (Triticum aestivum) (Piesik et al, 2006), acetaldehyde, methanol, isoprene, and additional C 6 compounds in common reed (Loreto et al, 2006), the essential oils pulgeone and menthone in the medicinal plant Minthostachys mollis (Banchio et al, 2005), as well as C 8 VOCs in the model liverwort species Marchantia polymorpha (Kihara et al, 2014), were identified and further investigated. In addition to DIVs found in agriculturally relevant species such as cotton (Gossypium hirsutum), Brussel sprouts (Brassica oleracea), and sweet potato (Ipomoea batatas) (Röse and Tumlinson, 2005;Connor et al, 2007;Meents et al, 2019), more recent studies included traditional medicinal plants and trees (Fontana et al, 2009;Martins et al, 2017;Kanagendran et al, 2018;Portillo-Estrada and Niinemets, 2018). Although the inclusion of a wider array of species highlights common DIV constituents, the potential as a functional DAMP yet remains to be verified for the majority of them.…”
Section: Mechanical Damage-induced Vocsmentioning
confidence: 99%